Porphyroblast inclusion trails: a new reference frame for correlating orogenic terrains - Sayab, M.; Aerden, D. (TRABAJOS DE GEOLOGÍA, 2010)
Tectonic and metamorphic correlation in ancient (Proterozoic) orogenic terrains has alwaysbeen problematic. This is because of the lack of a suitable reference frame to correlate deformation andmetamorphic events from one orogenic terrain to another. Measurement of porphyroblast inclusiontrails as Foliation Intersection/Inflection Axes (FIA) allows the chronological and kinematic linking ofdeformation as well as metamorphism. FIA measurements in the Mesoproterozoic Mount Isa andGeorgetown inliers of the North Australian Craton have revealed two separate orogenic events (O1 andO2), which not only correlate better within the orogen but also between the two terrains.Microstructural corelations have also been made with the Mesoproterozoic rocks of the SW USA.Hence, porphyroblast inclusion trails as FIA provide a new reference frame to help correlate orogenicterrains.